2019
DOI: 10.1002/cne.24676
|View full text |Cite
|
Sign up to set email alerts
|

New viral‐genetic mapping uncovers an enrichment of corticotropin‐releasing hormone‐expressing neuronal inputs to the nucleus accumbens from stress‐related brain regions

Abstract: Corticotropin‐releasing hormone (CRH) is an essential, evolutionarily‐conserved stress neuropeptide. In addition to hypothalamus, CRH is expressed in brain regions including amygdala and hippocampus where it plays crucial roles in modulating the function of circuits underlying emotion and cognition. CRH+ fibers are found in nucleus accumbens (NAc), where CRH modulates reward/motivation behaviors. CRH actions in NAc may vary by the individual's stress history, suggesting roles for CRH in neuroplasticity and ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 76 publications
8
32
0
Order By: Relevance
“…In addition, higher density of CRF-containing axonal projections from other brain areas was seen in the NAc compared with the DS. According to both the Allen Brain Atlas as well as a recent study by Itoga et al (2019), the BLA, BNST, and paraventricular nucleus of the thalamus send prominent CRF-containing projections to the NAc, but not the DS (Oh et al, 2014;Itoga et al, 2019). Thus, endogenously released CRF from CRFϩ cells or CRF-containing axonal projections to the NAc is predicted to potentiate ACh-dependent behaviors mediated by the NAc.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, higher density of CRF-containing axonal projections from other brain areas was seen in the NAc compared with the DS. According to both the Allen Brain Atlas as well as a recent study by Itoga et al (2019), the BLA, BNST, and paraventricular nucleus of the thalamus send prominent CRF-containing projections to the NAc, but not the DS (Oh et al, 2014;Itoga et al, 2019). Thus, endogenously released CRF from CRFϩ cells or CRF-containing axonal projections to the NAc is predicted to potentiate ACh-dependent behaviors mediated by the NAc.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have suggested that alternative sources of mPFC CRF may arise from the brainstem, such as from the CRF-expressing laterodorsal tegmental nucleus of the pons [53]. Recent work has further demonstrated a CRF-positive projection from the mPFC to the nucleus accumbens, suggesting a potential novel source of mPFC CRF distinct from the local interneuron population [54]. Further investigation is needed to determine the precise source of CRF relevant to these present findings.…”
Section: Discussionmentioning
confidence: 67%
“…Cells expressing this gene are slightly more dense in the posterior compared to anterior PVT, and expression in both subregions is largely medial and also denser than in the middle antero-posterior subregion of the PVT (Allen Institute, 2004 ). Prior research, in CRH-IRES-Cre mice, had identified considerable numbers of CRH + cells in the PVT (Peng et al, 2017 ), and also reported that they spanned the antero-posterior axis of the PVT, with somewhat higher density in the posterior portion of the PVT (Itoga et al, 2019 ). Using retrograde and anterograde viral tracing, these CRH + cells were found to send a major input to the nucleus accumbens (Itoga et al, 2019 ), although they may project to other regions as well.…”
Section: Distribution and Function Of Neuropeptides In The Paraventrimentioning
confidence: 99%
“…Prior research, in CRH-IRES-Cre mice, had identified considerable numbers of CRH + cells in the PVT (Peng et al, 2017 ), and also reported that they spanned the antero-posterior axis of the PVT, with somewhat higher density in the posterior portion of the PVT (Itoga et al, 2019 ). Using retrograde and anterograde viral tracing, these CRH + cells were found to send a major input to the nucleus accumbens (Itoga et al, 2019 ), although they may project to other regions as well. Despite the generation of a CRH-Cre rat (Pomrenze et al, 2015 ), it remains to be demonstrated that rats also express CRH in the PVT.…”
Section: Distribution and Function Of Neuropeptides In The Paraventrimentioning
confidence: 99%